MEDIA INFORMASI PENGENALAN RAMBU-RAMBU LALU LINTAS DI SATLANTAS POLRESTA JAMBI: Information Media, Interactive Media, Traffic Signs, Adobe Flash CS3 - Astari Prakasiwi, Degita (LP2M Universitas Nurdin Hamzah, 2018)
The lack of public awareness in obeying traffic signs is the main factors of the high traffic accidents. The reason is the number of rules of traffic signs that pretty much make the rider does not know and understand about the meaning of traffic signs. Therefore it is necessary for government to give more socialization to public about the importance of traffic signs. At the moment, the information media on traffic signs that exist today consists of books, public service ads and counseling by the police department are considered less effective, less interesting and less interactive. So, this study aims to design a media information about traffic signs. This media is designed to facilitate the rider or prospective rider to know and understand about the traffic signs. This media is designed using Adobe Flash CS3 Professional. This media is designed to introduce various traffic signs, in addition this media is also interactive. User can do a simple examination by answering some questions and the user will get the score.